Peran Pengawas Minum Obat (PMO) terhadap Kepatuhan Minum Obat Pasien TB Paru di Puskesmas Kecamatan Cakung Jakarta Timur - Revie Fitria Nasution; Markus Amay (STIKes Persada Husada Indonesia, 2015)
Pulmonary Tuberculosis patient PMO support greatly affect healing in medication. This study aimed to determine the role of PMO in preventing pulmonary TB transmission in the Work Area of Puskesmas Kecamatan Cakung Jakarta Timur. The type of research is a qualitative research with phenomenology approach in the Work Area of Puskesmas Kecamatan Cakung Jakarta Timur and 7 PMO as informants. The study was conducted by direct observation of the patient and the PMO residence, interviewing informants and secondary data obtained from the documents or records and reports of Puskesmas Remaja Samarinda. The results showed and improvement of environmental sanitation and tableware in health promotion by improved environmental, general and specific protection by bring round BCG immunization for newborn in the PMO, early diagnosis and prompt treatment by identification of the signs and symptoms of pulmonary TB and the search prompt treatment, limitation disability by supervisor of taking medication (PMO), and rehabilitation by increasing balanced nutrition. It is concluded that the role of PMO in preventing public health improvement efforts by health promotion, vaccination, family’s nutrition and regular medication.